Characterization of creep deformation and rupture behaviour of P92 steel weldment at 600°C - Nasrul Azuan, Alang (Faculty Mechanical Engineering, UMP, 2018)
P92 steel is a potential candidate for ultra-supercritical (USC) plant component. Thus, its suitability and performance for future service are still under investigation. Understanding the creep behaviour is essential to design the components that can sustain in service over a certain period. With the intention to investigate the creep deformation and rupture behaviour of P92 steel weldment, four cross-weld creep specimens were prepared and tested at 600°C at different stress levels. All specimens ruptured between 400 and 4,000 hours. Following the creep test, fractography examination was performed. P92 steel weldment exhibits clear primary, secondary and tertiary creep deformation stages. At long-term, the time portion for primary deformation as compared to rupture time reduces, however, secondary stage is observed to dominate. Deformation and rupture data obeys the power law relation which indicates the material deforms at a higher rate and rupture earlier as the stress increases. Ductility of P92 steel weldment reduces as the stress decreases. A strong correlation between minimum creep strain rate and time to rupture is observed when the data is fitted using original Monkman-Grant (MG) and Modified Monkman-Grant (MMG) relations. Examination of fracture surface reveals that at high stress, transgranular-type of fracture is dominant. As creep time increases, a mixture between the intergranular and transgranular fracture is evidence.